Temperature-dependent dielectric properties of human uterine fibroids over microwave frequencies. (27th October 2021) - Zia, Ghina; Sebek, Jan; Prakash, Punit
Abstract: Microwave ablation is under investigation as a minimally-invasive treatment for uterine fibroids. Computational models play a vital role in the development, evaluation and characterization of candidate ablation devices. The temperature-dependent dielectric properties of fibroid tissue are essential for accurate computational modeling. Objective: To measure the broadband temperature-dependent dielectric properties of uterine fibroids excised during hysterectomy procedures. Methods : The open-ended coaxial probe method was employed for measuring the broadband dielectric properties of freshly excised human uterine fibroid samples (n = 6) obtained from an IRB-approved tissue bank. The dielectric properties (relative permittivity, ε r, and effective electrical conductivity, σ eff ) were evaluated at temperatures ranging from 23 °C–150 °C, over the frequency range of 0.5–6 GHz. Linear piecewise parametrization with respect to temperature and quadratic parametrization with respect to frequency was applied to characterize broadband temperature-dependent dielectric properties of fibroid tissue. Results : The baseline room temperature values of ε r vary from 57.5 ± 5.29 to 44.5 ± 5.77 units and σ eff changes from 0.91 ± 0.19 to 6.02 ± 0.7 S m −1 over the frequency range of 0.5–6 GHz. At temperatures close to the water vaporization point, ε r, drops considerably i.e. to 12%–14% of its baseline value for all measured frequencies. σ eff values initially rise till 98 °C and then fall to 11%–13% of their baseline values at 125 °C for frequencies ≤2.45 GHz. The σ eff follows a decreasing trend for frequencies >2.45 GHz and drops to ∼6 % of their baseline room temperature values. Conclusion: The temperature dependent dielectric properties of uterine fibroid tissues over microwave frequency range are reported for the first time in this study. Parametric models of uterine fibroid dielectric properties are also presented for incorporation within computational models of microwave ablation of fibroids.